Numerical investigation and parametric analysis of PCM-based lightweight panels for wall's exterior cladding - Zeyad Amin Al-Absi; Muhammad Asif; Mohd Isa Mohd Hafizal (Case Studies in Thermal Engineering)
This study investigates the potential of lightweight cladding panels incorporating phase change materials (PCMFC) to enhance building energy efficiency and thermal comfort compared to the conventional cement render using numerical simulation. The numerical model was calibrated with experimental data showcasing average deviations below 1.27 %, affirming the high accuracy of the results. Subsequently, the numerical model was employed for parametric analyses to establish the optimal thickness and transition temperature for the PCMFC cladding panels. Results demonstrated that increasing panel thickness to a certain extent and selecting appropriate transition temperatures can significantly improve energy efficiency. Specifically, PCMFC cladding panels with a thickness of 3.0 cm and a transition temperature of 29 °C achieved the optimal performance, which reduced the estimated cooling load by up to 25.1 %. Finally, the year-round performance of the optimum PCMFC demonstrated substantial effectiveness in reducing annual discomfort time to 6 % in non-conditioned buildings, i.e., corresponding to CO₂ emissions reduction of 287.3 kg CO₂/year/m2, while lowering annual cooling energy by 22.1–50.3 % in conditioned buildings, i.e., CO₂ emissions reduction up to 63.5 kg CO₂/year/m2. These findings highlight the capacity of PCMFC cladding panels to improve overall thermal performance and minimize energy consumption, contributing to a more sustainable built environment.